Cybernetics approaches in intelligent systems for crops disease detection with the aid of IoT - Rathinam R.; Kasinathan P.; Govindarajan U.; Ramachandaramurthy V.K.; Subramaniam U.; Garrido S. (John Wiley and Sons Ltd, 2023)
Agricultural robots; Crops; Image enhancement; Image segmentation; Intelligent systems; Plants (botany); Water waves; Adversarial networks; Agricultural industries; Cluttered backgrounds; Contextual information; Disease detection; Internet of Things (IOT); Maximum accuracies; Maximum sensitivity; Internet of things